Optimal control model of money supply in economics - Дунаєва, Тамара Альбінівна; Гуськова, Надія Геннадіївна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
This paper presents the model describing the process of creating money. Developed and implemented optimization model of management the volume of money creation in the economy considering stochastic influences the dynamics of capital and destabilizing effects of the environment. We give comparative statistics and required values indicators by analysis of which we can conclude the feasibility of using models to calculate the equity commercial bank.